PELATIHAN PEMBUATAN WEBSITE SEBAGAI MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN SOFTWARE BERBASIS OPEN SOURCE BAGI GURU-GURU SMK BIDANG TI SE-PROPINSI DIY - Hariyanto, Didik; Yuniati, Nurhening; Mutaqin, Mutaqin (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
This training aims to apply science and technology on how to create a website that can be used as a learning media. Software that is used in this training is software based on open source. While the trainees are vocational teachers in IT (Information Technology) situated in the Province of DI. Yogyakarta. Training starts by registration of participants with the minimum re- quirements can operate the computer properly. At the beginning of training, participants were given pretest to determine initial capacity of participants about website development. Next, topic that starts from the introduction of internet, web server installation and CMS software installation. Then, the core topic is given on how to create websites as a learning media. Further topic is how to upload the website on the internet. Providing topic ends with providing independent tasks for each participant to create their own website as a learning media tailored to the field of teaching participants. At the end of the training, participants are given posttest. Final competency determi- nation based on participant self-assessment task, pretest and posttest. From the number of participants as many as 18 teachers, all can follow the training from beginning to end. In addition, teachers can com- plate all these tasks well independently, that is able to create websites as a learning media in good categories. From the results of pretest and posttest assessment also showed that the participants judged a good